2013
DOI: 10.3171/2012.9.jns12492
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cilostazol on cerebral vasospasm after aneurysmal subarachnoid hemorrhage: a multicenter prospective, randomized, open-label blinded end point trial

Abstract: Oral administration of cilostazol is effective in preventing cerebral vasospasm with a low risk of severe adverse events. Clinical trial registration no. UMIN000004347, University Hospital Medical Information Network Clinical Trials Registry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 50 publications
1
64
2
Order By: Relevance
“…This confirms the findings from the recently published cilostazol trial, in which an endothelial protective effect is attributed to elevating intracellular NO levels through the inhibition of phosphodiesterase 3 by using cilostazol. 26 Our findings also suggest that molsidomine targets the microvasculature, which may not be directly detectable by TCD or DSA.…”
Section: Discussionmentioning
confidence: 50%
“…This confirms the findings from the recently published cilostazol trial, in which an endothelial protective effect is attributed to elevating intracellular NO levels through the inhibition of phosphodiesterase 3 by using cilostazol. 26 Our findings also suggest that molsidomine targets the microvasculature, which may not be directly detectable by TCD or DSA.…”
Section: Discussionmentioning
confidence: 50%
“…Cilostazol inhibits phosphodiesterase 3 activity in smooth muscle cells and platelets, leading to relaxation of intact smooth muscle cells and inhibition of platelet aggregation. Thus, it attenuates cerebral vasospasm 18,19 and prevents endothelial damage, 20,21 which result in reduction of delayed cerebral ischemia after aneurysmal SAH. 22 In contrast to the younger group, in the older group ($60 years), the use of antiplatelet agents made the prognosis worse.…”
Section: Discussionmentioning
confidence: 96%
“…136 Cilostazol is a 2oxoquinoline derivative that inhib its phosphodiesterase 3 and has antithrombotic, vaso dilatory, antismooth muscle proliferation and cardiac inotropic and chronotropic effects. 137 A randomized, singleblind study of 109 patients undergoing clipping of ruptured aneurysms found that cilostazol significantly reduced angiographic vasospasm, DCI and cerebral infarction but had no effect on outcome. However, the sample size in this study was small.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…However, the sample size in this study was small. 137 Rescue therapies When a patient develops DCI, rescue therapies such as haemodynamic therapy or endovascular angioplasty are typically employed (Figures 4 and 5). Current recom mendations in the first few days after SAH and aneur ysm repair are to maintain euvolaemia, and to refrain from using prophylactic hypervolaemia, induced hyper tension or haemodilution.…”
Section: Clinical Trialsmentioning
confidence: 99%